Balancing Act: The Role of Community Based Governance and Pro Conservation Policies in Mitigating Threats to Ecotourism Sites in Cross River State, Nigeria - Maxwell-Borjor Achuk Eba (Universitas Negeri Makassar, 2026)
Ecotourism in Cross River State, Nigeria, holds significant potential for economic development, biodiversity conservation, and community empowerment. However, this potential is seriously threatened by deforestation, illegal logging, poaching, farmland encroachment, and weak enforcement of conservation laws. This study examines the role of community based governance and pro conservation policies in mitigating these threats to ecotourism sites, focusing on the Cross River National Park and the Afi Mountain Wildlife Sanctuary. Using a mixed methods approach that includes key informant interviews with park officials, community leaders, and ecotourism operators, as well as analysis of policy documents and enforcement records, the study finds that while Nigeria has a robust legal framework for conservation, including the National Park Service Act of 1999 and the Cross River State Forestry Commission Law of 2010, enforcement remains critically weak. Fines for illegal logging, for example, are as low as ₦200,000 per truck, which fails to deter commercial loggers. The study also finds that community based governance models, such as the proposed Community Tourism Association and existing joint forest management agreements, have shown promise in reducing encroachment and improving local stewardship, but they suffer from inadequate funding, weak institutional capacity, and lack of trust between communities and government agencies. The study concludes that effective mitigation of threats to ecotourism sites requires a balanced approach that combines stricter enforcement of pro conservation policies with genuine empowerment of local communities through benefit sharing arrangements, capacity building, and participatory governance structures. Recommendations include upward revision of fines for environmental crimes, establishment of community wildlife ranger programs, and formalization of community tourism agreements.